THE INFLUENCE OF ETHNOSCIENCE-BASED LEARNING ON CHEMISTRY TO THE CHEMISTRY’S LITERACY RATE OF THE PROSPECTIVE TEACHERS - Sumarni, Woro (Unnes Science Education Journal, 2018)
A research has been conducted to analyze the influence of ethnoscience-based chemistry learning to prospective teachers’ literacy of chemistry. The subjects of the research were 40 students of chemistry education. The instrument of chemistry literacy rate’s measurement were essays which are validated by experts’ judgement and trials. The result discovered that the implementation of ethnoscience-based learning in chemistry can improve students’ literacy in chemistry, specifically in the rate of medium to high on all group of students.